Strengthening UMKM Capacity Through Simple Cash Flow Training Based on Participatory Action Research (PAR): Penguatan Kapasitas UMKM Melalui Pelatihan Laporan Arus Kas Sederhana Berbasis Partisipatory Action Research (PAR) - Amalina, Nurhafifah; Anis, Idrianita; Yanti, Harti Budi; Dewi, R. Rosiyana; Fabiola, Livia (Yayasan Ahmar Cendekia Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a sector that contributes significantly to Indonesia’s economy; however, most still face fundamental challenges in financial management, particularly in cash flow recording. This condition affects their ability to maintain liquidity, measure profits, and plan business development. The focus of this community service program is to improve financial literacy through training in the preparation of simple cash flow statements for members of the Komunitas Sukses Berjamaah Indonesia (KSBI). The objective of the program is to equip MSME actors with technical skills in cash flow recording while fostering collective awareness of the importance of financial transparency and accountability. The method employed is a community-based participatory approach (Participatory Action Research/PAR) conducted through several stages: needs identification, module development, interactive training, hands-on practice, mentoring, and pre-test and post-test evaluations. The results of the program indicate significant improvements: understanding of cash flow concepts increased from 45% to 85%, the ability to prepare cash flow reports rose from 30% to 82%, awareness of separating personal and business finances improved from 25% to 78%, and skills in using digital applications grew from 20% to 75%. In addition to enhanced technical skills, the program also generated social changes, including disciplined financial recording, the emergence of local leaders, and the establishment of a culture of financial transparency.